Experiência, Circunstância, Projeto. Uma escola em Moçambique - Rita Maria Girbal Paulo Rodrigues (2020)
The following thesis comes from the request of a school that rose during a personal experience: a journey that took place in June 2019 aiming to help the victims of the Idai cyclone. It is intended to do an investigation underlying an appeal for the elaboration of a project for a school and residence in Mozambique. The investigation will be based in principals considered fundamental in the more elementary understanding of the meaning of architecture, with regard to its environmental aspect, in the specificity of intention and purpose, through reflections based in specialized bibliography, guided to a reality that, as it will be discerned, presents strong limitations. Understanding the climate and its constraints, investigating strategies in the field of education that are beneficial to the development of children, relating construction to the human body and its senses, it is intended that the spaces contribute to supporting communities that live in a context of great precariousness. It is also desired for this dissertation to be the beginning of a dialogue between the different parts, the architect and the people. Emphasizing the importance of memory and the intrinsic culture to the African communities of the region, bringing vernacular strategies to the proposal, local materials and unskilled labor to the concretization of the ideia that will be launched. The equipments proposed, are oriented towards promoting an environment that opens the opportunity for multiple children to receive education, a crucial factor in development, improvement of living conditions and consequent prosperity.